Seasonal Differences in Relative Gene Expression of Putative Central Appetite Regulators in Arctic Charr (Salvelinus alpinus) Do Not Reflect Its Annual Feeding Cycle - Striberny, Anja; Ravuri, Chandra Sekhar; Jobling, Malcolm; Jørgensen, Even Hjalmar (PLOS ONE, 2015)
The highly seasonal anadromous Arctic charr (Salvelinus alpinus) was used to investigate the possible involvement of altered gene expression of brain neuropeptides in seasonal appetite regulation. Pro-opiomelanocortin (POMCA1, POMCA2), Cocaine and amphetamine regulated transcript (CART), Agouti related Peptide (AgRP), Neuropeptide Y (NPY) and Melanocortin Receptor 4 (MC4-R) genes were examined. The function of centrally expressed Leptin (Lep) in fish remains unclear, so Lep (LepA1, LepA2) and Leptin Receptor (LepR) genes were included in the investigation. In a ten months study gene expression was analysed in hypothalamus, mesencephalon and telencephalon of immature charr held under natural photoperiod (69°38’N) and ambient temperature and given excess feed. From April to the beginning of June the charr did not feed and lost weight, during July and August they were feeding and had a marked increase in weight and condition factor, and from November until the end of the study the charr lost appetite and decreased in weight and condition factor. Brain compartments were sampled from non-feeding charr (May), feeding charr (July), and non-feeding charr (January). Reverse transcription real-time quantitative PCR revealed temporal patterns of gene expression that differed across brain compartments. The non-feeding charr (May, January) had a lower expression of the anorexigenic LepA1, MC4-R and LepR in hypothalamus and a higher expression of the orexigenic NPY and AgRP in mesencephalon, than the feeding charr (July). In the telencephalon, LepR was more highly expressed in January and May than in July. These results do not indicate that changes in central gene expression of the neuropeptides investigated here directly induce seasonal changes in feeding in Arctic charr.